FINANCIAL CONSTRAINT AND PERFORMANCE OF NIGERIAN FIRMS: GENDER DIVERSITY AS MODERATOR - Muhammed Alhaji Abubakar; Nurnaddia Nordin; Nurhaiza Nordin; Yusuf Babatunde Adeneye (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This research evaluated the role of gender diversity as a moderator, on financial constraints and performance of firms listed on the Nigerian Stock Exchange (NSE). Financial constraint was proxied by the KZ index, while accounting and market-based performance were measured by return on assets and Tobin’s Q respectively. The data from 87 firms were processed using descriptive statistics, correlation, and regression. The data was taken from financial reports from 2016 to 2021. According to the results, there is a considerable and adverse impact of financial constraints on both performance indicators. The outcome also demonstrates how gender diversity enhances corporate performance and lessens financial constraints. Based on the findings, having more female board members minimizes financial constraint issues by lowering agency costs and information asymmetry. It also improves business performance. However, it was found that while financial constraints have a significant and adverse influence on performance of Nigerian enterprises, gender diversity helps to mitigate these effects. Therefore, suggests that in order to encourage prospects for Nigerian companies to acquire financing, there should be a greater representation of women on corporate boards. This will lessen problems with financial constraints and enhance the performance of Nigeria’s non-financial companies.